PKM Pembuatan Sistem Pengolahan Air Limbah Sederhana dan Pegelolaan Limbah Cair Tahu dengan Metode Fotodegradasi - Gusliani Eka Putri; Wiya Elsa Fitri; Inge Angelia; Oktariyani Dasril; Edison , (Jurnal Abdimas Saintika, 2020)
Natural Tofu Business has been established since 1999. The Natural Tofu Business already has a Waste Water Treatment System( WWTS) but it was not in accordance with the standards. This condition can have a negative impact on the environment because the natural tofu business was located near to the river. Purpose of community service to improve knowledge about liquid waste management, training to design WWTS that was good and training in the management of liquid waste with photodegradation techniques. The methods used are lectures, discussions, questions and answers, and demonstrations (practice). The results from these community service activities were increased respondents' knowledge about tofu liquid waste, forming a good WWTS consisting of 4 wastewater storage tanks. Photodegradation techniques can reduce of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) of tofu liquid waste after photocatalysts were added for 2 and 4 hours with sunlight irradiation so that liquid waste was safely disposed of in the river. This photodegradation technique was proven effective in decomposing liquid waste that needs to be developed in the future.